Expand your horizons with the diverse and informative answers found on IDNLearn.com. Our platform offers reliable and detailed answers, ensuring you have the information you need.

"Solving Equations by Completing the Square: m^2+2m-48=-6

Sagot :

[tex]m^2+2m-48=-6 \\ \\ m^2+2m-48+6=0\\ \\m^2+2m-42=0\\ \\a=1, \ b= 2, \ c= -42 \\ \\\Delta = b^{2}-4ac = 2^{2}-4*1*(-42)= 4+168 =172 \\\\\sqrt{\Delta }=\sqrt{172} =\sqrt{4*43}=2\sqrt{43}\\ \\x_{1}=\frac{-b-\sqrt{\Delta }}{2a} =\frac{-2-2\sqrt{43}}{2}=\frac{2(-1-\sqrt{43})}{2}= -1-\sqrt{43} \\ \\x_{2}=\frac{-b+\sqrt{\Delta }}{2a} = \frac{-2+2\sqrt{43}}{2}=\frac{ 2(-1+\sqrt{43})}{2}= -1+\sqrt{43}[/tex]
[tex]m^2+2m-48=-6\\\\m^2+2m\cdot1+1^2-1^2=-6+48\\\\(m+1)^2-1=42\\\\(m+1)^2=42+1\\\\(m+1)^2=43\iff m+1=-\sqrt{43}\ \vee\ m+1=\sqrt{43}\\\\m=-1-\sqrt{43}\ \vee\ m=-1+\sqrt{43}[/tex]